Online Language learning Facilitation: New Demands, Students’ Viewpoints, and Material Development - Mohsen Karimian Azimi (UICELL, 2020)
The Post Corona World has automatically brought about new conditions in language learning and instruction. The impacts and consequences of the pandemic on ELT would make part of the paper at hand. Some conceptual issues would accordingly be part and parcel of the propositions discussed throughout the initial part of this short paper. On the latter part, the paper discusses the viewpoints of some 49 participants sought through the final run of the modified questionnaire, among other means, developed and administered to the students of online classes to see how they feel about the rest of the process. Positive as well as negative points of online language instruction are categorically delineated to help enhance the instruction in prospect. The part which might have positively benefited most regarding the present circumstances is the material development domain by lowering the panic of the instructor in developing the material which might not only be much more appealing to the students but also help them enhance their language ability. Proposals for further research in several areas close the paper